Antifungal Cream Preparation of Galangal Rhizome Extract (Alpinia galanga L.) - Rety Setyawaty; Feriadi Feriadi; Dewanto Dewanto (Faculty of Pharmacy, Universitas Gadjah Mada, 2019)
Cream is a semi-solid emulsion dosage form of both water-in-oil (W/O) or oil in water (O/W) type containing one or more dissolved or dispersed ingredients in the corresponding base material (containing no less than 60% water). Cream is usually used as emollient or containing active pharmaceutical ingredients on the skin (Ansel, 2008). The advantage of cream are the application practicallity, water washeability, and the easiness to spread evenly. In this research, we formulated cream containing rhizome Galangal rhizome. According to Darmono (2008), Galangal rhizome has various properties such as antifungal and antibacterial activities. Galangal rhizome contains 1-asetoksikhavikol asetat (ACA). ACA is an antifungal. ACA has good solubility in 70% ethanol. We maserated Galangal rhizome (Alpinia galangal L.) to extract ACA from the simplicia. As for the cream base, we use hidrophilic base containing emulgators stearic acid and triethanolamine, with glycerin as humectant. During the optimization, we chose three formulas, formula 1 (10% stearic acid , 2% triethanolamin, 5% glycerin, and 0.01% vitamin E), formula 2 (15% stearic acid , 3% triethanolamin, 10% glycerin, and 0.05% vitamin E), and formula 3 (20% stearic acid, 4% triethanolamin, 7.5% glycerin, and 0.09% vitamin E). We used the bases to contain 10% of the extract. The results show that formula 1, formula 2, and formula 3 had typical smell of Galangal rhizome, brown color, and thick consistency. All formulas are homogenous. Formula 1 the best stability. We conclude that Galangal rhizome (Alpinia galanga L.) can be formulated in cream form with our formula 1 had the best stability among others.